PROTEIN FRACTIONS OF BLOOD SERUM IN CHICKENS, VACCINATED WITH INACTIVATED VACCINES AGANST RESPIRATORY MYCOPLASMOSIS OF POULTRY - Обуховська, О. В.; Руденко, О. П.; Матюша, Л. В.; Попова, О. М. (Scientific Progress & Innovations, 2013)
It is proved that the double intramuscular introduction of inactivated vaccines against respiratory mycoplasmosis of poultry will help to increase albumin and γ-globulin in the blood serum of chickens, indicating activation of the immune system. The use of a vaccine based on inactivated bacterinum increases to 47.0% albumin level and γ-globulin to 91.9% on the 21-st day after the second injection. Using by a similar scheme of subunit vaccine based on the unintegrated bacmass increases by 39.6% albumins loevel and γ-globulins by 84.2%, respectively.